Action research on building a stabilization initiative in response to a crisis - Bermudez, Marc Lester A. (Animo Repository, 2021)
The insider action research (IAR) is about building a stabilization initiative in response to COVID-19 for a micro, family-owned business, Azriel Gel-Pack. The IAR provided me an opportunity to fulfill my current role as marketing lead of the company and an action researcher at the same time for my Master of Business Administration (MBA) degree. The action research is composed of two cycles that serves as company’s response to the impacts of COVID-19 such as mobility/workforce restrictions and employee safety. These are: (a) restructuring manpower schedule based on stakeholder priorities and (b) creating of health & safety company policies As learned throughout the journey, stakeholder consultations, especially the subordinates, via bottom-up approach to problem solving, is very critical in achieving better results. Through the bottom-up approach, priorities can be identified and considered when building solutions. Frameworks involving employee scheduling factors and factors affecting conditions of work are employed and used for extrapolation. Keywords: family business, COVID-19 stabilization initiative, health & safety policy